Thymosin β4 Up-regulation of MicroRNA-146a Promotes Oligodendrocyte Differentiation and Suppression of the Toll-like Proinflammatory Pathway - Santra, Manoranjan (American Society for Biochemistry and Molecular Biology, 2014)
Thymosin β4 (Tβ4), a G-actin-sequestering peptide, improves neurological outcome in rat models of neurological injury. Tissue inflammation results from neurological injury, and regulation of the inflammatory response is vital for neurological recovery. The innate immune response system, which includes the Toll-like receptor (TLR) proinflammatory signaling pathway, regulates tissue injury. We hypothesized that Tβ4 regulates the TLR proinflammatory signaling pathway. Because oligodendrogenesis plays an important role in neurological recovery, we employed an in vitro primary rat embryonic cell model of oligodendrocyte progenitor cells (OPCs) and a mouse N20.1 OPC cell line to measure the effects of Tβ4 on the TLR pathway. Cells were grown in the presence of Tβ4, ranging from 25 to 100 ng/ml (RegeneRx Biopharmaceuticals Inc., Rockville, MD), for 4 days. Quantitative real-time PCR data demonstrated that Tβ4 treatment increased expression of microRNA-146a (miR-146a), a negative regulator the TLR signaling pathway, in these two cell models. Western blot analysis showed that Tβ4 treatment suppressed expression of IL-1 receptor-associated kinase 1 (IRAK1) and tumor necrosis factor receptor-associated factor 6 (TRAF6), two proinflammatory cytokines of the TLR signaling pathway. Transfection of miR-146a into both primary rat embryonic OPCs and mouse N20.1 OPCs treated with Tβ4 demonstrated an amplification of myelin basic protein (MBP) expression and differentiation of OPC into mature MBP-expressing oligodendrocytes. Transfection of anti-miR-146a nucleotides reversed the inhibitory effect of Tβ4 on IRAK1 and TRAF6 and decreased expression of MBP. These data suggest that Tβ4 suppresses the TLR proinflammatory pathway by up-regulating miR-146a.